Evaluation of Roholtiella sp. Extract on Bell Pepper (Capsicum annuum L.) Yield and Quality in a Hydroponic Greenhouse System - Bello, Adewale Suraj; Saadaoui, Imen; Ahmed, Talaat; Hamdi, Helmi; Cherif, Maroua; Ben-Hamadou, Radhouane (Frontiers in Plant Science, 2022)
This study was carried out to investigate the impacts of cyanobacteria (Roholtiella sp.) high-value product extract HVPE and water resuspended biomass WRB treatments on bell pepper production using the hydroponic system under greenhouse conditions. Six cyanobacteria treatments (6 mL L-1, 4 mL L-1, and 2 mL L-1 - HVPE, 6 mL L-1, 4 mL L-1, and 2 mL L-1 – WRB, and TR0 as control) were evaluated using the foliar application method. The results showed that foliar application of HVPE with treatments 2 mL L-14 mL L-1, 6 mL L-1 produced significant higher values of physical growth parameters of bell pepper plants (shoot length, the number of leaves, plant leaf length, plant leaf width, the diameter of the shoot), SPAD index, yield components (the fruit length, fruit width, the number of fruit per plant, and fresh weight per fruit), biochemical composition (ascorbic acid, phenolic acid, and total soluble solids (TSS)) and the total yield compared to the control group TR0. Also, significant higher values of growth parameters (shoot length, the number of leaves, plant leaf length, plant leaf width, the diameter of the shoot), SPAD index, yield components (the fruit length, fruit width, the number of fruit per plant, and fresh weight per fruit), biochemical composition i.e. ascorbic acid, phenolic acid, and total soluble solids (TSS) and the total yield were obtained with foliar spraying WRB at 2 mL L-1, 4 mL L-1, and 6 mL L-1 compared to the control group TR0. Consequently, the treated bell pepper with Roholtiella sp. HVPE and WRB were more efficient in enhancing production and chemical constituents compared with the control group.